Antisense transcription regulates the expression of the enterohemorrhagic Escherichia coli virulence regulatory gene ler in response to the intracellular iron concentration. - Toru Tobe; Hilo Yen; Hiroki Takahashi; Yoko Kagayama; Naotake Ogasawara; Taku Oshima (PLoS ONE)
Enteric pathogens, such as enterohemorrhagic E. coli (EHEC) O157:H7, encounter varying concentrations of iron during their life cycle. In the gastrointestinal tract, the amount of available free iron is limited because of absorption by host factors. EHEC and other enteric pathogens have developed sophisticated iron-responsive systems to utilize limited iron resources, and these systems are primarily regulated by the Fur repressor protein. The iron concentration could be a signal that controls gene expression in the intestines. In this study, we explored the role of iron in LEE (locus for enterocyte effacement) virulence gene expression in EHEC. In contrast to the expression of Fur-regulated genes, the expression of LEE genes was greatly reduced in fur mutants irrespective of the iron concentration. The expression of the ler gene, the LEE-encoded master regulator, was affected at a post-transcription step by fur mutation. Further analysis showed that the loss of Fur affected the translation of the ler gene by increasing the intracellular concentration of free iron, and the transcription of the antisense strand was necessary for regulation. The results indicate that LEE gene expression is closely linked to the control of intracellular free iron homeostasis.